2002
DOI: 10.1046/j.1472-4642.2002.00161.x
|View full text |Cite
|
Sign up to set email alerts
|

Are there predictable clines in plant–pollinator interactions along altitudinal gradients? The example of Cytisus scoparius (L.) Link in the Sierra de Guadarrama (Central Spain)

Abstract: Abstract. We analyse the hypothesis that predictable gradients occur in plant–pollinator interactions along altitudinal gradients due to thermal constraints on insect body size and floral traits being selected for by pollinators. Pollinators’ size should follow Bergmann's rule in mountains (larger body size at higher altitudes) and selection should, in turn, lead to larger flower size at higher altitudes. The study focuses on the flower and pollinator size variation in 11 Cytisus scoparius populations located … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
51
1
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 35 publications
0
51
1
4
Order By: Relevance
“…Pollinator 1463 communities tend to change with increasing elevation (and decreasing temperature). At 1464 higher altitudes the average size of pollinators increases (Malo and Baonza, 2002), but 1465 pollinator abundance is lower (Arroyo et al, 1982). In addition, flies tend to become the 1466 dominant pollinator group, mainly because other groups are restricted to lower areas (Kearns, 1467(Kearns, 1992).…”
Section: Effects Of Altitude 1461mentioning
confidence: 99%
See 2 more Smart Citations
“…Pollinator 1463 communities tend to change with increasing elevation (and decreasing temperature). At 1464 higher altitudes the average size of pollinators increases (Malo and Baonza, 2002), but 1465 pollinator abundance is lower (Arroyo et al, 1982). In addition, flies tend to become the 1466 dominant pollinator group, mainly because other groups are restricted to lower areas (Kearns, 1467(Kearns, 1992).…”
Section: Effects Of Altitude 1461mentioning
confidence: 99%
“…In the Rocky Mountains (United States of America), flies replace bees as the main 1468 pollinators (Kearns 1992), while in the Andes of South America, tachinid flies and 1469 hummingbirds replace bee flies (Bombyliidae) and bees at higher altitudes (Arroyo et al, 1470(Arroyo et al, 1982. In addition, flower size tends to increase (Malo and Baonza, 2002). The lower 1471 pollinator abundance results in lower pollinator to flower ratios and lower seed set in plants at 1472 higher altitudes (Arroyo et al, 1985;Malo and Baonza, 2002).…”
Section: Effects Of Altitude 1461mentioning
confidence: 99%
See 1 more Smart Citation
“…2009; Takahashi and Yoshida 2009;Maad et al 2013), lower numbers of flowers (Kelly 1998;Baret et al 2004;Maad et al 2013) and lower numbers of flower heads (Asteraceae family) (Kelly 1998;Alexander et al 2009), but larger flower sizes (Kudo and Molau 1999;Malo and Baonza 2002;Herrera 2005;Maad et al 2013). In addition, along with an increase in elevation, plants possess higher plasticity of flower longevity (Trunschke and Stöcklin 2017), increase clonality, tend to be older (Št'astná et al 2012) and produce more flowering shoots (von Arx et al 2006).…”
mentioning
confidence: 99%
“…However, plant species with wide elevational ranges are expected to be exposed to different selective pressures at low and high elevations (Frei et al 2014a), and this may result in non-linear responses in some traits along the elevational gradient. For example, Malo and Baonza (2002) in their study on plant-pollinator interactions along an elevational gradient found that the Cytisus scoparius flower size in the mountains of Central Spain had a unimodal relationship with elevation and the maximum size occurred at the intermediate elevation. This curvilinear, unimodal relationship may be explained as a result of the trade-off between pollinator selection for larger flowers in higher elevations (e.g.…”
mentioning
confidence: 99%